A Method to Extract Measurable Indicators of Coastal Cliff Erosion from Topographical Cliff and Beach Profiles: Application to North Norfolk and Suffolk, East England, UK. - Muñoz-López, Pablo; Payo, Andrés; Ellis, Michael A.; Criado-Aldeanueva, Francisco; Jenkins, Gareth Owen (MDPI, 2020)
The present study contributes to our understanding of a poorly known aspect of cliff–beach interaction and outlines a quantitative approach that allows for simple analysis of widely available topographical elevation profiles, enabling the extraction of measurable indicators of coastal erosion.
Keywords: Geofísica; Playas - Erosión; Modelos en geología; Cliff behaviour; Cliff recession; Erosion; Beach wedge area (BWA); Space-for-time substitution; Ergodic system